1985
DOI: 10.1016/0377-8401(85)90001-x
|View full text |Cite
|
Sign up to set email alerts
|

The voluntary intake and digestibility of combinations of cereal crop residues and legume hay for sheep

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 3 publications
8
24
1
1
Order By: Relevance
“…However, the animals on the autoclaved EC diets consumed more grass than others on concentrate. Several reports indicate that supplementation of basal grass diets improves feed intake and liveweight gains [19] [20]. The liveweight changes in this study were higher for biodegraded EC diets but not significantly different from the grass diet which had least liveweight gain.…”
Section: Resultssupporting
confidence: 51%
“…However, the animals on the autoclaved EC diets consumed more grass than others on concentrate. Several reports indicate that supplementation of basal grass diets improves feed intake and liveweight gains [19] [20]. The liveweight changes in this study were higher for biodegraded EC diets but not significantly different from the grass diet which had least liveweight gain.…”
Section: Resultssupporting
confidence: 51%
“…AFRC (1993) guidelines suggest that 20 kg male wethers require about 3.8 MJ metabolisable energy (ME) daily for maintenance. Mosi and Butterworth (1985) reported MS intakes of 2.9 MJ ME, while in this study (using a value of 5.7 MJ ME/kg MS calculated from the OM digestibility values (MAFF, 1984) obtained in the digestibility study) with observed intakes of 0.35 kg DM, it is unlikely that the negative controls consumed much above 2.0 MJ ME daily, and hence their continual loss of body condition over the feeding study.…”
Section: Discussionmentioning
confidence: 48%
“…For instance, lignin contents of the MS residues for the negative control, CC, forage and dual-purpose types at 150 and 300 g supplementation treatments were 10, 8, 9, 9, 10 and 8 g lignin/kg DM, respectively. Interestingly, Mosi and Butterworth (1985) observed that animals offered MS alone showed less selectivity against lignin than when supplemented with trifolium hay, suggesting a degree of substitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence the overall nutritive value of the coarse-stemmed CR may be very low in some circumstances. Among the small cereals, oat straw is generally considered to have the highest nutritive value, followed by barley, wheat, and rye straw, and with rice straw having the lowest value (Dias-da-Silva and Guedes, 1990;Mosi and Butterworth, 1985).…”
Section: Variation In Composition and Digestibilitymentioning
confidence: 99%